Ameliorative effect of hesperidin on ligation‐induced periodontitis in rats. Issue 3 (27th September 2018) - Kuo, Po‐Jan; Fu, Earl; Lin, Chi‐Yu; Ku, Cheng‐Te; Chiang, Cheng‐Yang; Fu, Martin MJ; Fu, Min‐Wen; Tu, Hsiao‐Pei; Chiu, Hsien‐Chung
Abstract: Background: This study evaluated the ameliorative effect of hesperidin (HES), an anti‐inflammatory flavanone, in rats with ligation (Lig)‐induced periodontitis. Methods: A total of 48 rats were randomly divided into non‐ligation group (NL), Lig group, and two ligation‐plus‐HES groups (L+H). HES was administered immediately after ligature placement at a dose of 75 or 150 mg/kg by intragastric feeding. Destruction of the ligated maxillary second and mandibular first molars were evaluated by dental radiography, microcomputed tomography (micro‐CT), and histometry performed after sacrificing the rats on the seventh day. The expression levels of interleukin (IL)‐1β, IL‐6, and inducible nitric oxide synthase (iNOS) messenger (m)RNAs in the gingiva were determined by reverse‐transcription polymerase chain reaction. The expression of iNOS was examined by immunohistochemistry. Results: The dental radiography and micro‐CT findings revealed significantly increased alveolar bone loss in the Lig group, which was significantly prevented by HES. The histometry results revealed less gingival inflammation and connective tissue loss in the L+H groups compared with that in the Lig group. The mRNA expression levels of IL‐6, IL‐1 β, and iNOS were significantly increased in the Lig group but were reduced in the L+H groups. The immunostaining results showed that the ligation‐induced iNOS expression was also decreased by HES. Conclusions: Oral administration of HES promotes an ameliorative effect against the ligation‐induced alveolar bone loss and effectively inhibits the production of proinflammatory mediators in rats with experimentally induced periodontitis. Therefore, HES may be a good candidate for modulating oral inflammatory diseases.